Difference between revisions of "2025 AIME II Problems/Problem 2"

(Solution 1)
(Solution 1)
Line 16: Line 16:
  
 
<math>\Rightarrow 3(n-2)+\frac{39}{n+2} \in Z</math>
 
<math>\Rightarrow 3(n-2)+\frac{39}{n+2} \in Z</math>
 +
 +
<math>\Rightarrow \frac{39}{n+2} \in Z</math>
  
 
Since n+2 is positive,the positive factor of 39 are 1, 3, 13 and 39
 
Since n+2 is positive,the positive factor of 39 are 1, 3, 13 and 39
  
So x=-1, 1, 11 and 37
+
So n=-1, 1, 11 and 37
  
Since x is positive, so x=1, 11 and 37
+
Since n is positive, so n=1, 11 and 37
  
 
1+11+37=  <math>\framebox{49}</math> is the correct answer
 
1+11+37=  <math>\framebox{49}</math> is the correct answer
  
 
~Tonyttian [https://artofproblemsolving.com/wiki/index.php/User:Tonyttian]
 
~Tonyttian [https://artofproblemsolving.com/wiki/index.php/User:Tonyttian]

Revision as of 21:15, 13 February 2025

Problem

Find the sum of all positive integers $n$ such that $n + 2$ divides the product $3(n + 3)(n^2 + 9)$.

Solution 1

$\frac{3(n+3)(n^{2}+9) }{n+2} \in Z$

$\Rightarrow \frac{3(n+2+1)(n^{2}+9) }{n+2} \in Z$

$\Rightarrow \frac{3(n+2)(n^{2}+9) +3(n^{2}+9)}{n+2} \in Z$

$\Rightarrow 3(n^{2}+9)+\frac{3(n^{2}+9)}{n+2} \in Z$

$\Rightarrow \frac{3(n^{2}-4+13)}{n+2} \in Z$

$\Rightarrow \frac{3(n+2)(n-2)+39}{n+2} \in Z$

$\Rightarrow 3(n-2)+\frac{39}{n+2} \in Z$

$\Rightarrow \frac{39}{n+2} \in Z$

Since n+2 is positive,the positive factor of 39 are 1, 3, 13 and 39

So n=-1, 1, 11 and 37

Since n is positive, so n=1, 11 and 37

1+11+37= $\framebox{49}$ is the correct answer

~Tonyttian [1]